PENGEMBANGAN BUKU ELEKTRONIK TRIGONOMETRI DENGAN MENGINTEGRASIKAN PENALARAN MATEMATIS, TEKNOLOGI, SEJARAH, DAN APLIKASI TRIGONOMETRI - Ika Wulandari; Mardiyana Mardiyana; Tri Atmojo Kusmayadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research aimed (1) to formulate the need of trigonometric book content, (2) to develop prototype into trigonometric electronic book, and (3) to find out the result of evaluation on the feasibility of electronic book developed for teachers’ candidates, teachers, and trigonometric instructors. A research and development method was used to provide a trigonometric electronic book. This method encompassed the following stages: (1) exploring: analyzing library study and case study, (2) developing: designing the product until it became a trigonometric electronic book, and (3) evaluating: studying  the feasibility of trigonometric electronic book. The results were reveals as follows: 1) The identification of trigonometric content should pay attention to: (a) geometric reasoning and understanding such as: symbol, distance, pythagorean theorem, circle, triangle, angle, and pi concept, (b) function reasoning and understanding such as: representation (numeric, chart, symbolic/algebraic, verbal), and representation interrelationship, (c) trigonometric function reasoning and understanding such as: definitions of function based on unit circle, based on right triangle side ratio, multiple representation and property in trigonometric main function, (d) history and the chronology of trigonometric function inception, and (e) the application of trigonometric function in real world. 2) The development of prototype into trigonometric electronic book was conducted with the following procedures: (a) design analysis based on the identification of book content need, (b) the development of book content, (c) the alignment of illustration, chart, table, game, video and layout, (d) designing the application (.exe), electronic book pdf and html, 3) Expert judgment: material expert rated 4.07 (Good), media expert rated 4.03 (Good). The result of evaluation showed that: (a) in Trial I, the product users’ candidates rated 4.95 (Very Good) for material aspect and 4.8 (Very Good) for media aspect, (b) in Trial II, the product users’ candidates rated 4.79 (Very good) for material aspect, and 4.61 (Very Good) for media aspect. Considering the result of feasibility test of materials and media expert, trials I and II for feasibility test of users’ candidates, this trigonometric electronic book was feasible to be used as the handout for the students as teachers’ candidates, teachers, and trigonometric instructors.Keywords: trigonometric electronic book, mathematic reasoning, technology, history, and trigonometric application.